Dynamic Control of the Self-Assembling Properties of Cyclodextrins by the Interplay of Aromatic and Host-Guest Interactions - Neva, Tania; Carmona, Thais; Benito, Juan M.; Przybylski, Cédric; Ortiz Mellet, Carmen; Mendicuti, Francisco; García Fernández, José M. (Frontiers in Chemistry, 2019)
The presence of a doubly-linked naphthylene clip at the O-2I and O-3II positions in the secondary ring of -cyclodextrin (CD) derivatives promoted their self-assembly into head-to-head supramolecular dimers in which the aromatic modules act either as cavity extension walls (if the naphthalene moiety is 1,8-disubstituted) or as folding screens that separate the individual CD units (if 2,3-disubstituted). Dimer architecture is governed by the conformational properties of the monomer constituents, as determined by NMR, fluorescence, circular dichroism and computational techniques. In a second supramolecular organization level, the topology of the assembly directs host-guest interactions and, reciprocally, guest inclusion impacts the stability of the supramolecular edifice. Thus, inclusion of adamantane carboxylate, a well-known CD cavity-fitting guest, was found to either preserve the dimeric arrangement, leading to multicomponent species, or elicit dimer disruption. The ensemble of results highlights the potential of the approach to program self-organization and external stimuli responsiveness of CD devices in a controlled manner while keeping full diastereomeric purity.